Technical quality and patient perception of hospital care quality - Mohamed, Bahari; Mohamad, Meriati; Azizan, Noor Azlinna (WIDAD University college, 2017)
The purpose of this study is to examine the effects of technical quality (medical care and nursing care) on perceived service quality, patient satisfaction and behavioural compliance at a public hospital. This study is also to confirm the mediating effects of patient satisfaction between perceived service quality and behavioural compliance.A structured questionnaire was distributed to discharged patients who warded at the hospital for at least two days. To analyze the relationship between constructs, Smart PLS analysis technique was used. The findings provided empirical evidence that medical care and nursing care significantly influenced perceived service quality, patient satisfaction and behavioural compliance. Patient satisfaction mediated the perceived service quality and behavioural compliance. The results reveal that medical care and nursing care are the outstanding factors to determine perceived service quality, patient satisfaction and behavioural compliance. By evaluating the healthcare service quality, it is hoped to provide an insight to healthcare managers about the service quality dimensions and their relationship with patient satisfaction, and behavioural compliance.Although the concepts of perceived service quality, patient satisfaction, and behavioural compliance are explored frequently in healthcare service literature, there are few researches that focus on the effect of medical care and nursing care on discharged patients.